Prevention of cervical, vaginal, and vulval cancers: role of the quadrivalent human papillomavirus (6, 11, 16, 18) recombinant vaccine - Maria Lina Diaz (Dove Medical Press, 2009)
Maria Lina DiazSection of Ambulatory Gynecology Cleveland Clinic Florida Weston, Florida, USAAbstract: The relationship between the human papillomavirus (HPV) and malignancies of the uterine cervix, vagina, and vulva has been established. The development of a quadrivalent HPV recombinant prophylactic vaccine represents the first time in history that primary prevention of these cancers is offered to girls and women. The prevalence of oncogenic HPV subtypes in cervical cancers has been the most studied, but prevalence has also been established for vaginal and vulvar cancers. Clinical trials demonstrate impressive efficacy in disease prevention as well as excellent safety and tolerability. The role the quadrivalent HPV recombinant vaccine promises to have in the reduction of gynecologic malignancies will depend on various factors, including acceptance and accessibility of the vaccine, duration of immunity, and cross-protection against other oncogenic HPV subtypes. The HPV vaccine’s role in disease reduction will probably be viewed in the context of a strategy that involves continued secondary screening and lifestyle modification to reduce modifiable risk factors, along with widespread vaccination.Keywords: human papillomavirus, quadrivalent vaccine, cervical cancer, vaginal cancer, vulvar cancer